Unequal security protection for secure multimedia communication - Yiu-Wing Leung; Hou, Ricky Yuen-Tan (2015 IEEE 4th Global Conference on Consumer Electronics (GCCE), 2015)
In some multimedia communication applications for portable devices, the media should be encrypted for confidentiality and privacy. Since portable devices have relatively limited resources, it would be desirable if these resources could be better utilized to give better security protection to the media. In this paper, we study and optimize a new method, called unequal security encryption, which applies multiple encryption methods (with different security strength and processing time) to encrypt different parts of the media (with different importance). This method can provide better security protection subject to the given computing resources for encryption.